Discovering Islands of Competence through Play: Experiences of Individuals with a Learning Disability. Issue 4 (2nd October 2021) - O'Malley, John A.; Teman, Eric D.; Dzik, Paulina W.
ABSTRACT: Students in K–12 settings who are identified with a Learning Disability (LD) often struggle with the formation of their self-identity within the traditional school setting. Because previous research has shown that play can be instrumental in the creation of a person's self-identity, play can be especially important for those who have a LD. This article presents the lived and told stories of play using narrative inquiry of five individuals who were identified with a LD during their K–12 experience. The stories are organized under a single plot line under the theme "islands of competence, " a metaphor coined by Dr. Robert Brooks which highlights the importance of play in positive self-identity through social, recreational, and creative activities. Recommendations for counselors toward implementing play for clients with a LD based on the lived and told stories through narrative inquiry.